Mathematical Model for Information Technology Infusion for Healthcare Sector in Nigeria - idowu, PETER ADEBAYO; BALOGUN, JEREMIAH ADEMOLA; egejuru, ngozi chidozie (IGI Global, 2023)
Vol.2, No.2 DOI: 10.4018/IJCCP.2017070101